Combination of KRAS gene silencing and PI3K inhibition for ovarian cancer treatment - Kim, Min Ju; Lee, So Jin; Ryu, Ju Hee; Kim, Sun Hwa; Kwon, Ick Chan; Roberts, Thomas M. (ELSEVIER, 2020)
The phosphoinositide 3-kinase (PI3K) and RAS signaling pathways are frequently co-activated and altered during oncogenesis. Owing to their regulatory cross-talk, the early attempts of targeting only one pathway have mostly ended up promoting the development of drug resistance. Here, we propose using small interfering RNA (siRNA) therapeutics to directly target the undruggable KRAS (siKRAS) in combination with the pan-PI3K inhibitor GDC-0941 (GDC) to simultaneously block both PI3K and RAS signaling, thereby exerting synergistic anti-tumor effects on ovarian cancers with PTEN deficiency and KRAS(G12D) mutation. For successful delivery of siKRAS, tGC/psi-nanoparticle formulation of polymerized siRNA and thiol-modified glycol chitosan nanoparticle-was used for KRAS specific inhibition in vitro and in vivo. GDC or siKRAS monotherapy each impede downstream signaling, leading to some delay in cell proliferation and migration. When combined, however, they engender much higher inhibition of PI3K signaling and stimulation of apoptosis in an ovarian allograft model compared to monotherapies. Our results show the feasibility of developing new combination strategies for the management of multiple oncogenic mutations activating PI3K and RAS signaling.
Keywords: CELLULAR UPTAKE; MEK INHIBITORS; SIRNA DELIVERY; CROSS-TALK; RESISTANCE; PATHWAY; RAS; ISOFORM; NANOPARTICLE; P110-ALPHA